Dissipation and residue of ethephon in maize field - Jian-nan DONG; Yong-qiang MA; Feng-mao LIU; Nai-wen JIANG; Qiu JIAN (Journal of Integrative Agriculture, 2015)
A rapid and reliable method was developed for analysis of ethephon residues in maize, in combination with the investigation of its dissipation in field condition and stabilities during the sample storage. The residue analytical method in maize plant, maize kernel and soil was developed based on the quantification of ethylene produced from the derivatization of ethephon residue by adding the saturated potassium hydroxide solution to the sample. The determination was carried out by using the head space gas chromatography with flame ionization detector (HS-GC-FID). The limit of quantification (LOQ) of the method for maize plant was 0.05, 0.02 mg kg−1 for maize kernel and 0.05 mg kg−1 for soil, respectively. The fortified recoveries of the method were from 84.6–102.6%, with relative standard deviations of 7.9–3.8%. Using the methods, the dissipation of ephethon in maize plant or soil was investigated. The half life of ethephon degradation was from 0.6 to 3.3 d for plant and 0.7 to 5.7 d for soil, respectively. The storage stabilities of ethephon residues were determined in fresh and dry kernels with homogenization and without homogenization process. And the result showed that ethephon residues in maize kernels were stable under −18°C for 6 mon. The results were helpful to monitor the residue dissipation of ethephon in the maize ecosystem for further ecological risk assessment.